2017
DOI: 10.3390/antiox6010006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Oxidative Stress Responses in the Pediatric Population

Abstract: Adults demonstrate an upregulation of their pro- and anti-oxidant mechanisms in response to acute exercise while systematic exercise training enhances their antioxidant capacity, thereby leading to a reduced generation of free radicals both at rest and in response to exercise stress. However, less information exists regarding oxidative stress responses and the underlying mechanisms in the pediatric population. Evidence suggests that exercise-induced redox perturbations may be valuable in order to monitor exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 90 publications
1
26
0
Order By: Relevance
“…Treatment with NADPH oxidase inhibitors decreased reactive oxygen species (ROS) production in adipose tissue and attenuated dysregulation of adipocytokines, improved diabetes, hyperlipidemia, and hepatic steatosis [5].A bout of high intensity exercise induces excessive ROS production that is linked with lipid and peroxidation, having deleterious impact on cells and tissues [9]. However, regular exercise with proper intensity is an effective way to prevent and improve obesity by increasing the activation of antioxidant enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GPx), resulting in alleviation of oxidative stress [10][11][12][13]. In a study by Baghaiee et al, eight weeks of aerobic exercise significantly decreased serum levels of malondialdehyde (MDA) (an oxidative stress marker in obese subjects) and significantly increased SOD-2 gene expression [12].…”
mentioning
confidence: 99%
“…Treatment with NADPH oxidase inhibitors decreased reactive oxygen species (ROS) production in adipose tissue and attenuated dysregulation of adipocytokines, improved diabetes, hyperlipidemia, and hepatic steatosis [5].A bout of high intensity exercise induces excessive ROS production that is linked with lipid and peroxidation, having deleterious impact on cells and tissues [9]. However, regular exercise with proper intensity is an effective way to prevent and improve obesity by increasing the activation of antioxidant enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GPx), resulting in alleviation of oxidative stress [10][11][12][13]. In a study by Baghaiee et al, eight weeks of aerobic exercise significantly decreased serum levels of malondialdehyde (MDA) (an oxidative stress marker in obese subjects) and significantly increased SOD-2 gene expression [12].…”
mentioning
confidence: 99%
“…It should be taken in account that SOD levels usually increase with exercise among adult populations [52]. However, oxidative stress responses to exercise and the underlying mechanisms in the pediatric population are still unclear [53]. Therefore, not only diet matters, and it might be mandatory that CD children exercise for a better prognosis of the disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its physiological importance, scarce information is available regarding the effects of repeated exercise on oxidative stress in healthy children [ 12 , 13 ]. High levels of oxidative stress markers in children and adolescents have been reported, possibly due to a high flow of oxygen to the working muscles, and/or due to their immature antioxidant defense systems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, antioxidant reserves may be lower in children, especially those engaged in chronic intensive training programs; suggesting that children, and probably adolescents, may be susceptible to exercise-induced oxidative damage [ 14 ]. So, the knowledge of exercise induced oxidative stress responses would be valuable for children and adolescents engaged in systematic strenuous exercise [ 12 ]. However, no studies of oxidative stress biomarkers have been found in children during an exercise made in competition, and in tennis in particular.…”
Section: Introductionmentioning
confidence: 99%